Conjunctival malignant melanoma in a young immunocompetent male patient: clinical presentation and management—a case report - Mohammed Alhamood; Bashar Sbh; Ali Muhammad; Imad Saadeh (Journal of Medical Case Reports)
Abstract Background Conjunctival melanoma is a rare yet aggressive ocular surface malignancy, with an incidence of approximately 0.2–0.8 cases per million individuals annually. It predominantly affects older adults, making its occurrence in younger individuals exceedingly rare and diagnostically challenging. Case presentation We report a 30-year-old Syrian male presenting with a progressively enlarging pigmented lesion on the temporal-inferior conjunctiva of the right eye. The lesion, noted since adolescence, demonstrated significant growth over the past 3 years. Comprehensive clinical assessment and imaging studies confirmed the presence of a well-vascularized, mobile conjunctival lesion, with no evidence of intraocular extension. Surgical excision with 1 mm safety margins was performed, followed by ocular surface reconstruction using a cryopreserved amniotic membrane graft. Histopathological analysis revealed a malignant melanoma with epithelioid and spindle cell morphology and tumor-free margins. Postoperative recovery was uneventful, with full epithelialization by 1 week and no evidence of recurrence at the 1-year follow-up. Conclusion Timely diagnosis and a multidisciplinary surgical approach are essential for achieving optimal outcomes in conjunctival melanoma, particularly in young patients. Complete excision with negative margins combined with amniotic membrane grafting ensures effective oncologic control and functional ocular surface restoration.